The influence of Security Sector in governance, case study of the Zimbabwe National Army from 1980 to 2015 - Mupanganyama, Hopewell (2017)
The paper examines the influence of the security sector in governance, a case study of Zimbabwe National Army from 1980 till 2015. Such a topic has been necessitated culminating from Zimbabwe experiencing the deployment of military personnel to strategic positions in various state institutions responsible for governance hence affecting economic and political governance positively and negatively. The research aims to find out why the ZNA fail to divorce itself from the ruling party ZANU PF in issues of governance. It aims to assess the internal and external operations as well as economic and political operations which have been carried out by the Zimbabwe National Army which has both positive and negative effects to governance. It also examines the achievements and challenges within the Zimbabwe National Army in promoting good governance. The researcher also covers the gape which various scholars failed to cover in the literature view concerning this topic. Many theories were also included to support the research topic. This research also take into consideration stakeholders’ perspectives on factors behind the influence of the ZNA in governance and among the stakeholders include ZANU PF, ZNA, MDC T officials to mention but a few. The research is qualitative in nature. Also the research put into consideration both the primary the secondary sources. Questionnaires and interviews were used to collect data. Tables only were used to represent the results. The results obtained from this research shows that the influence of the security sector in governance issues is inextricably linked hence it affects governance issues positively and negatively. Recommendations and future suggestions presented in this research is of paramount importance.